Relationships between movements of the lower limb joints and the pelvis in open and closed kinematic chains during a gait cycle - Svoboda, Zdenek; Janura, Miroslav; Kutilek, Patrik; Janurova, Eva (Journal of human kinetics, 2016)
Lots of athletic skills performed during practice or competition are initiated by the legs, where athletes either walk or run prior to executing specific skills. Kinematic chains are used to describe the relationships between body segments and joints during movement. The aim of this study was to determine the relationships between movements of lower limb segments and the pelvis in open and closed kinematic chains while walking. The experimental group consisted of 32 males (age 23.3 ± 2.5 years, body mass 78.1 ± 8.7 kg, body height 182 ± 6 cm). For 3D analysis, an optoelectronic system Vicon MX (7 cameras, frequency 200 Hz) was used. Positioning of the segments was determined by the PlugInGait Model. Each participant executed five trials at speeds ranging from 1.38 to 1.52 m·s-1. The relationships between angle variables of the lower limbs and the pelvis in selected gait cycle phases were evaluated using STATISTICA software (version 10.0) and the Spearman correlation. The highest numbers of moderate and large correlations were found at opposite toe off, heel rise and initial contact for the sagittal and transversal planes in comparison to the frontal plane. The closed kinematic chain had a stronger impact on determining the movement pattern. The instructions or interventions focusing on closed kinematic chain alternation are more effective for changes in a movement pattern. The preferred limb initiates kinematics in the direction of propulsion, while the non-preferred limb in internal and external rotation.
Keywords: coupling; walking; intra-limb; coordination